PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL SANCA BERBASIS S.id UNTUK MENINGKATKAN MINAT BACA SISWA - Apri Kartikasari H.S; Pramesti Dwi Nurahma; Dienta Yanu Anggita; Wafiq Yasfin Abdillah (Universitas Negeri Medan, 2026)
Readings skills are one of the competencies that must be mastered by students. V-grade students at SDN Ngale 2, Paron District, Ngawi Regency have low reading interest due to the lack of innovative learning media used. This is the basis for this research which aim to: design a digital learning media design based on S.id; 2) process the development of digital learning media based on S.id to provide stimulation to students to like reading more. This development research uses the ADDIE model. Of the five stages, only the Analyze, Design, and Development stages are carried out. The design results collaborate Canva, FlipHTML5 Flipbook applications to create digital comics, and Youtube for content about reading. Meanwhile, the process of developing digital learning media called SANCA (Sahabat Anak Suka Baca) which contains audio-video containing material about reading and a digital comic entitled Legenda Golan dan Mirah, a folk tale originating from Ponorogo Region, into the S.id microsite to facilitate its use.